EFEKTIVITAS PROGRAM PASAR BEBAS PLASTIK DI CITRALAND FRESH MARKET DALAM MENDUKUNG PENGURANGAN PENGGUNAAN KANTONG PLASTIK DI KOTA SURABAYA - Shenny Kusumaningtyas; Diana Hertati (Journal Publicuho, 2024)
The problem of plastic waste in Indonesia is a problem that has not been resolved to date. This research aims to find out and describe the effectiveness of the Plastic Free Market Program at Citraland Fresh Market in supporting the reduction of plastic bag use in the city of Surabaya. The type of research used in this research is descriptive qualitative. This research uses Sutrisno's effectiveness theory which states that there are four focuses, namely understanding the program, being on target, being on time, achieving goals and real change. The data collection techniques used in this research were interviews with informants, direct observation in the field, and documentation. Then the data analysis model used in this research is data collection, data presentation, data condensation, as well as drawing conclusions and verification. The results of this research indicate that the effectiveness of the Plastic Free Market Program at Citraland Fresh Market in supporting the reduction of plastic bag use in the city of Surabaya has not been carried out effectively. This happens because it is not on target. There are still traders who provide plastic bags which are considered cheaper. Then visitors are still found using plastic bags brought from home because they are considered easier to carry anywhere.